“It Is Like a Feeling”: Theorizing Emotion in Mathematics through Complex Embodiment - Rachel Lambert; David Hernández-Saca; Rebeca Mireles-Rios; Marilyn Monroy Castro (Mathematics, 2022)
Conversations of educational equity in mathematics necessitate a more deliberate, nuanced look at the mathematical processes of learning for students of color from historically marginalized communities. This paper describes the theoretical work of a research collaborative that seeks to develop understanding of the experiences around mathematical identity of Latinas labeled with Learning Disabilities in mathematics classrooms. Expanding the theory of Complex Embodiment from Disability Studies, we explore new interdisciplinary theoretical and methodological tools to analyze the emotional, embodied experience of learning mathematics in the social worlds of mathematics classrooms, using emotional discourse. We take up theoretical and methodological practices around intersectionality through analysis of how power and positioning operate in mathematics identity development. We find that the young woman whose narratives we explore in this paper is positioned through deficit discourses around disability and multilingual learners, yet she understands herself through a positive mathematical affinity she shares with her mother. Over time, we see her narratives shift emotionally away from mathematics, as well as away from this connection with her mother. Her narratives help us develop a theoretical perspective that understands emotion in mathematics learning as both embodied and socially constructed.